SYNTHESIS OF CU-AG NANOPARTICLES ON TITANIUM AS CATHODE TO THE ELECTROCHEMICAL REDUCTION OF NITRATE FOR AQUEOUS SOLUTIONS - La Rosa-Toro Gómez, Adolfo (2023)
Nitrate pollution poses a significant challenge to both the environment and human health. This study focuses on exploring the electrochemical reduction of nitrate (ERN) has been studied using new cathodes based on Cu-Ag nanoparticles coated onto titanium (Cu-Ag /Ti). The nanoparticles were synthesized by galvanic displacement technique. These were characterized by DLS, UV-Vis analysis.For its use as a cathode, pretreated titanium plates were coated with Cu-Ag nanoparticles. These cathodes were characterized by FE-SEM, EDS analysis and electrochemical measurements. The FE-SEM imagery revealed spherical shapes with an averages size of ≤ 100nm, displaying signs of stability even after 40 hours of reaction. The EDS analysis indicated an atomic composition ratio of 6/1 (Cu/Ag).Electrochemical characterization demonstrated superior electrocatalysis in the proposed cathode evaluated in solution of 100mg L-1 NO3-N + 0,03 M Na2SO4 as a supporting electrolyte, IrOx/Ti as counter electrode and Ag/AgCl (3 M) as reference electrode.By chronopotentiometry was compared Ti, Cu/Ti, Cu-Ag /Ti (N1 y N2) with a current density 20 mA cm-2 over 5 hours of reaction to. REN 1-cell reactor with 40 mA cm-2 by Ti, Cu-Ag /Ti (N1 y N2) cathodes for 3,5 hours was 22, 62, 28, 28, 38, 58 and 47, 61 reduced %NO3-N respectively.